Should NS5A inhibitors serve as the scaffold for all-oral anti-HCV combination therapies? - Janardhan SV (Dove Medical Press, 2015)
Sujit V Janardhan, Nancy S Reau Center for Liver Diseases, Section of Gastroenterology, Hepatology, and Nutrition, Department of Medicine, University of Chicago, Chicago, IL, USA Abstract: Chronic hepatitis C virus (HCV) infection represents a global health problem that affects up to 130–150 million people worldwide. The HCV treatment landscape has been transformed recently by the introduction of direct-acting antiviral (DAA) agents that target viral proteins, including the NS3 protease, the NS5B polymerase, and the NS5A protein. Treatment with multiple DAAs in combination has been shown to result in high rates of sustained virologic response, without the need for pegylated interferon, and a shorter duration of therapy compared with interferon-based regimens; however, the optimal combination of DAAs has yet to be determined. The class of NS5A inhibitors has picomolar potency with pangenotypic activity, and recent clinical studies have shown these inhibitors to be an important component of DAA combination regimens. This review discusses the rational design of an optimal anti-HCV DAA cocktail, with a focus on the role of NS5A in the HCV life cycle, the attributes of the NS5A class of inhibitors, and the potential for NS5A inhibitors to act as a scaffold for DAA-only treatment regimens. Keywords: hepatitis C virus, NS5A, therapy, direct-acting antiviral